2021
DOI: 10.1007/s10549-020-06074-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of radiomics and machine learning with dynamic contrast-enhanced magnetic resonance imaging for patients with atypical ductal hyperplasia in predicting malignant upgrade

Abstract: Purpose To investigate whether radiomics features extracted from magnetic resonance imaging (MRI) of patients with biopsy-proven atypical ductal hyperplasia (ADH) coupled with machine learning can differentiate high-risk lesions that will upgrade to malignancy at surgery from those that will not, and to determine if qualitatively and semi-quantitatively assessed imaging features, clinical factors, and image-guided biopsy technical factors are associated with upgrade rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Radiomics-based analysis of breast cancer has emerged to become a well-investigated research focus in assessing its potential for predicting various endpoints, such as relapse, progression-free survival, subtype, or tumor phenotyping [ 7 , 8 , 9 , 10 , 13 , 14 , 23 , 24 , 25 ]. PCR after NAC has been shown to imply prolonged disease-free and overall survival [ 26 ] and has therefore been proposed as a surrogate early clinical endpoint for long-term survival [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics-based analysis of breast cancer has emerged to become a well-investigated research focus in assessing its potential for predicting various endpoints, such as relapse, progression-free survival, subtype, or tumor phenotyping [ 7 , 8 , 9 , 10 , 13 , 14 , 23 , 24 , 25 ]. PCR after NAC has been shown to imply prolonged disease-free and overall survival [ 26 ] and has therefore been proposed as a surrogate early clinical endpoint for long-term survival [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the last consensus conference, several studies reported an upgrade rate of ADH into malignancy (DCIS or invasive cancer) between 7.3 and 57% in targeted OE. Consequently, the majority of these studies recommended OE, although increasingly considering other options such as imaging follow-up after VAB, when the calcifications in clinical imaging have been completely removed [6,19,[22][23][24][25][26][27][28][29][30][31]. In the MIBB database, patients with ADH underwent OE in the majority of cases (62.7%), and an upgrade rate of 25.2% was observed.…”
Section: Current Evidence For Underestimation After Cnb/vabmentioning
confidence: 99%
“…Over the past few years, a number of publications have investigated the potential of radiomics-based analyses for determination of different genomic and phenotypic characteristics of breast cancer as well as more fundamental features such as grading or metastatic spread [9,10,32]. Leithner et al published a study focused exclusively on DCE-MRI for the differentiation of two important tumor characteristics, by means of molecular subtype and receptor status.…”
Section: Discussionmentioning
confidence: 99%